Multimodal Combined Anesthesia during Traumatic Operations - Ye. S. Gorobets; V. Ye. Gruzdev; A. V. Zotov; D. A. Tipisev; A. R. Shin (Общая реаниматология, 2009)
Any need for combining the effective antinociceptive defense of a patient during traumatic surgical interventions has give rise to multimodal combined anesthesia (MCA) comprising a combination of epidural analgesia with a small-dose local anesthetic (ropivacaine 2 mg/ml), an opioid (fentanyl 2 ^g/ml), and adrenaline (2 ^g/ml) with low-flow anesthesia with sevoflurane at low concentrations (Key words: multimodal anesthesia, traumatic operations, epidural analgesia, sevoflurane anesthesia, anesthetic safety, massive blood loss.